The Pact of Free Cities – Addressing Rule of Law Problems from a Local Perspective - Claudia Matthes (Polish Political Science Yearbook, 2023)
Since December 2020, the Pact of Free Cities, founded by the mayors of the Visegrád capitals, has expressed the dire wish not to be held hostage for their national governments’ disrespect for the rule of law. Being cut off from financial support out of political intentions, they lobby for direct EU support. The article explores the dynamics of this initiative, its strategies to reach out to European institutions and their resonance, as well as the meaning of the Pact’s city diplomacy from a democratic perspective. The analysis of various documents published by the Pact of Free Cities shows how it combines its efforts to promote democracy, the rule of law and sustainable policies by engaging on the EU level. The Pact developed a distinct type of urban experimentalism that established a new link between the European and the city level.